Effects of heating and moisture of the mechanical properties of composites - Sim, Jing Kai (2019)
Composite materials have been widely used in aerospace in applications such as engine blades, brackets, interiors, rotors and body wings. While flying, composite materials can experience moisture and heat damage resulting in delamination. Hence, this reduces the strength properties and wear resistance of the composite materials which can lead to unfortunate tragic. Carbon fiber reinforces polymer and glass fiber reinforced polymer were used for heating and moisture in this project. It was fabricated in the composite laboratory using the autoclave machine. Hence, this report will study the effect of heating and moisture of the mechanical properties of composites. It is to see how heating and moisture will affect the mechanical properties of these composites. Non-destructive testing methods such as ultrasonic test were used in this project to detect the internal defects of the composite materials caused by heating and moisture. Furthermore, mechanical testing such as hardness test and tensile test were conducted on the composite materials. This study aims to see whether the ultrasonic test can predict the mechanical properties of the composite materials.